Quantum computation and search algorithms: a historical overview and introduction - Eliasson, Leif (My University, 2020)
Quantum computation is the study of the information processing tasks which may be accomplished using quantum mechanical systems. At the heart of inquiries to ascertain the potential of quantum computation is the question of whether it is possible for a quantum computer to efficiently solve computational problems which have no efficient solution on a classical computer. Pioneering work done by David Deutsch, Peter Shor, Lov Grover and others in the 1980s and 1990s established a great deal of the essential theoretical framework and results which provided answers to this question which has justified continued research and interest in quantum computing ever since. Today we will provide a brief historical and functional overview of the development of quantum computing and its applications during this time, and contrast it with classical computing, and in particular, we will examine Grover’s algorithm as an illustrative example of the potential benefits of quantum search algorithms.
Presented in absentia on April 27, 2020 at "Student Research Day" at MacEwan University in Edmonton, Alberta. (Conference cancelled)
Keywords: quantum computing; Grover’s algorithm